Scenes on earth : Explorations on landscape and characters on moving images - Tania Granada Moreno (2025)
This master thesis deals with the relationship between natural landscapes and characters in time-based media. It focuses on the tension of proximity and distance between these features in the context of narrative moving images. The subjects are explored by means of an artistic research, producing as results an audiovisual installation and a written report. The multi-channel audiovisual installation creates a cinematic environment in spatial and material dimensions, where places turn into characters and humans as part of the landscape. The written report positions the research within a theoretical and an artistic context, as well as documents the making of the installation. Both works highlight the tension of either facing a landscape or being a part of it, in an attempt to embrace an ecological approach to how the living environment is portrayed and how stories are told about being in the world.
Keywords: landscape and characters; landscape in moving images; landscape as character; ecological visual narrative; proximity and distance